Short- and long-term effects of 56Fe irradiation on cognition and hippocampal DNA methylation and gene expression. (December 2016) - Impey, Soren; Jopson, Timothy; Pelz, Carl; Tafessu, Amanuel; Fareh, Fatema; Zuloaga, Damian; Marzulla, Tessa; Riparip, Lara-Kirstie; Stewart, Blair; Rosi, Susanna; Turker, Mitchell; Raber, Jacob
Abstract Background Astronauts are exposed to56 Fe ions that may pose a significant health hazard during and following prolonged missions in deep space. We showed previously that object recognition requiring the hippocampus, a structure critical for cognitive function, is affected in 2-month-old mice irradiated with56 Fe ions. Here we examined object recognition in 6-month-old mice irradiated with56 Fe ions, a biological age more relevant to the typical ages of astronauts. Moreover, because the mechanisms mediating the detrimental effects of56 Fe ions on hippocampal function are unclear, we examined changes in hippocampal networks involved in synaptic plasticity and memory, gene expression, and epigenetic changes in cytosine methylation (5mC) and hydroxymethylation (5hmC) that could accompany changes in gene expression. We assessed the effects of whole body56 Fe ion irradiation at early (2 weeks) and late (20 weeks) time points on hippocampus-dependent memory and hippocampal network stability, and whether these effects are associated with epigenetic changes in hippocampal DNA methylation (both 5mC and 5hmC) and gene expression. Results At the two-week time point, object recognition and network stability were impaired following irradiation at the 0.1 and 0.4 Gy dose, but not following irradiation at the 0.2 Gy dose. No impairments in object recognition or network stability were seen at the 20-week time point at any irradiation dose used. Consistent with this pattern, the significance of pathways for gene categories for 5hmC was lower, though not eliminated, at the 20-week time point compared to the 2-week time point. Similarly, significant changes were observed for 5mC gene pathways at the 2-week time point, but no significant gene categories were observed at the 20-week time point. Only the 5hmC changes tracked with gene expression changes. Conclusions Dose- and time-dependent epigenomic remodeling in the hippocampus following56 Fe ion exposure correlates with behavioral changes.